The role of endoscopy in the small intestinal transplant recipient: A review. Issue 5 (9th December 2020) - Crismale, James F.; Mahmoud, Dalia; Moon, Jang; Fiel, M. Isabel; Iyer, Kishore; Schiano, Thomas D.
Abstract: Intestinal transplantation (ITx) is the treatment of choice for patients with intestinal failure who have developed life‐threatening complications related to long‐term parenteral nutrition. Patients may also undergo ITx as part of a combined liver‐intestine or multivisceral transplant for a variety of indications, most commonly intestinal failure‐associated liver disease or porto‐mesenteric thrombosis. Endoscopy plays a critical role in the posttransplant management of these patients, most commonly in the diagnosis and management of rejection, which occurs in up to 30–40% of patients within the first‐year posttransplant. With a lack of noninvasive biomarkers to identify the presence of rejection, endoscopy and biopsy remain the gold standard for its diagnosis. Endoscopic evaluation of the graft is also important in the identification of other complications post‐ITx, including posttransplant lymphoproliferative disorder, graft‐versus‐host disease, and enteric infections. Each patient's posttransplant anatomy may be slightly different, making endoscopy sometimes technically challenging and necessitating clear and frequent communication with the surgical team in order to help identify the highest yield approach. Herein, we review the most common pathologies found endoscopically in the post‐ITx patient and describe some of the unique challenges the endoscopist faces when evaluating these complex patients. Abstract : Endoscopy plays a critical role in the diagnosis and management of complications following intestinal transplantation.